PsycEXTRA Dataset 2007
DOI: 10.1037/e424162008-001
|View full text |Cite
|
Sign up to set email alerts
|

Pilot test of new roadside survey methodology for impaired driving

Abstract: AcknowledgementsThe authors would like to acknowledge the extensive assistance we received from State and local officials in the conduct of this project. The data collection procedures we were developing and testing were not routine by any means and the willingness of State officials to help us identify cooperating local police agencies and the agencies' willingness to participate in the project were obviously essential to our success.Many individuals provided the assistance described above, but in each jurisd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…When marijuana is found in drivers, however, it is often in conjunction with alcohol, where an impairing effect is more likely. The most prevalent drug detected in the pilot study was marijuana (Lacey et al, 2007). There appeared to be a strong positive correlation between the oral fluid and blood tests, and the only discrepancies found in the pilot study (negative oral fluid and a positive blood) were from 10 cases in which the inactive metabolites were detected in blood but not the active tetrahydrocannabinol (THC).…”
Section: Selection Of Drugs For Screening and Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…When marijuana is found in drivers, however, it is often in conjunction with alcohol, where an impairing effect is more likely. The most prevalent drug detected in the pilot study was marijuana (Lacey et al, 2007). There appeared to be a strong positive correlation between the oral fluid and blood tests, and the only discrepancies found in the pilot study (negative oral fluid and a positive blood) were from 10 cases in which the inactive metabolites were detected in blood but not the active tetrahydrocannabinol (THC).…”
Section: Selection Of Drugs For Screening and Analysismentioning
confidence: 86%
“…Findings above 100 percent are due to slight variations in the amount of the substances actually added to the scientific control samples (scientific error). For a more thorough discussion of the Quantisal device, see the pilot study report (Lacey et al, 2007).…”
Section: Oral Fluid Collection Devicementioning
confidence: 99%
See 1 more Smart Citation
“…It may be impossible to obtain reliable research data on blood drug concentrations among random drivers on a voluntary basis. Studies in the USA have shown an unacceptably high refusal rate of 50-60% if collecting blood, even when 50 US$ was offered as incentive for providing a sample [3,4]. However, in a study performed in the Netherlands Aim: To estimate the prevalence of driving with blood drug concentrations above the recently proposed Norwegian legal limits for drugged driving in random traffic.…”
Section: Introductionmentioning
confidence: 98%
“…Self-report data on controversial issues, such as drug use and driving, are often underreported. For example, in the pilot study preceding the current study (Lacey, Kelley-Baker, Furr-Holden, Brainard, & Moore, 2007), only about a third of the persons who tested positive for drugs other than alcohol reported they had used drugs within the past year, and only 2% reported such drug use on the night of the survey. This underreporting occurred even though the respondents knew they were being tested for the presence of drugs.…”
Section: Introductionmentioning
confidence: 99%